Association of Socio-Economic Position with Technique Failure and Mortality in Australian Non-Indigenous Peritoneal Dialysis Patients. Issue 4 (July 2017) - Chan, Samuel; Cho, Yeoungjee; Koh, Yung H.; Boudville, Neil C.; Clayton, Philip A.; McDonald, Stephen P.; Pascoe, Elaine M.; Francis, Ross S.; Mudge, David W.; Borlace, Monique; Badve, Sunil V.; Sud, Kamal; et al.
Background: Few studies have examined the relationship between socio-economic position (SEP) and peritoneal dialysis (PD) outcomes, particularly at a country level. The aim of this study was to investigate the relationships between SEP, technique failure, and mortality in PD patients undertaking treatment in Australia. Methods: The study included all Australian non-indigenous incident PD patients between January 1, 1997, and December 31, 2014, using Australia and New Zealand Dialysis and Transplant (ANZDATA) Registry data. The SEP was assessed by quartiles of postcode-based Australian Socio-Economic Indexes for Areas (SEIFA), including Index of Relative Socio-economic Advantage and Disadvantage (IRSAD – primary index), Index of Relative Socio-economic Disadvantage (IRSD), Index of Economic Resources (IER), and Index of Education and Occupation (IEO). Technique and patient survival were evaluated by multivariable Cox proportional hazards survival analyses. Results: The study included 9, 766 patients (mean age 60.6 ± 15 years, 57% male, 38% diabetic). Using multivariable Cox regression, no significant association was observed between quartiles of IRSAD and technique failure (30-day definition p = 0.65, 180-day definition p = 0.68). Similar results were obtained using competing risks regression. However, higher SEP, defined by quartiles of IRSAD, was associated with better patient survival (Quartile 1 reference; Quartile 2 adjusted hazards ratio [HR] 0.96, 95% confidence interval [CI] 0.86 – 1.06; Quartile 3 HR 0.87, 95% CI 0.77 – 0.99; Quartile 4 HR 0.86, 95% CI 0.76 – 0.97). Similar results were found when IRSD was analyzed, but results were no longer statistically significant for IER and IEO. Conclusions: In Australia, where there is universal free healthcare, SEP was not associated with PD technique failure in non-indigenous PD patients. Higher SEP was generally associated with improved patient survival.